Framing, partisan predispositions, and public opinion on climate change. (March 2015) - Wiest, Sara L.; Raymond, Leigh; Clawson, Rosalee A.
Highlights: Local framing increases perceptions of problem severity and support for local policy action. Benefit framing weakens perceptions of problem severity and support for local policy action. Local framing increases some behavioral intentions to address climate change. Framing effects vary for different partisan predispositions. Abstract: We investigate how different framing of climate change impacts affects public opinion on the issue. Using an experimental design, we examine the influence of frames presenting local versus global climate impacts and frames discussing projected losses versus those also discussing possible benefits of climate change, on individual perceptions of the severity of climate change, behavioral intentions to address climate change, and attitudes toward climate change policies. The results indicate that our impact frames influence public opinion, although the effects sometimes differ based on individuals' partisan predispositions. Specifically, our study shows that local frames increase perceptions of the severity of the problem and support for local (sub-national) policy action for all subjects, as well as behavioral intentions for subjects who are Independents or Republicans. Presenting subjects with information on the potential benefits and losses of climate change weakens perceptions of problem severity for all subjects at the local and national level, decreases support for local policy action among Democrats, and has no effect on behavioral intentions. Overall, these results are consistent with policy research suggesting that perceptions of local vulnerability are an important factor in the adoption of sub-national climate change policies. The findings also imply that the effectiveness of particular climate change impact frames will vary from one state to another depending on a state's partisan leanings.